Associated factors with suicidal ideation and chronic pain in elderly patients assisted in a general hospital of the city of Buenos Aires - Brienza, Héctor L.; Matusevich, Daniel L.; Lapelle, María V.; Pagotto, Vanina L.; Faccioli, José L. (Revista del Hospital Italiano de Buenos Aires, 2020)
Introduction: the following study aimed to explore some demographic characteristics associated with chronic pain and the development of suicidal ideas in a population of patients over 65 years.Method: an cross-sectional observational and analytical study was carried out by collecting data from clinical histories of patients over 65 years of age who attended the external offices of the geriatrics team of the Psychiatry service of the Italian Hospital of Buenos Aires between June 2018 and December 2018.Results: a total of 222 patients were included in the study, of which 50 (23%) presented indicators of chronic pain and 33 patients (14.6%) had suicidal ideation. A correlation study established that being employed, suffering from chronic pain and having had more than one psychiatric hospitalization are factors that increase the risk of presenting suicidal ideation. The variables suicidal ideation, age, and separated or divorced marital status compared to being married are factors associated with the presence of chronic pain.Conclusions: chronic pain and suicidal ideation are factors that contribute to increasing frailty in elderly patients and should be studied in greater depth to understand the different modes of expression of psychiatric pathology in this population
Keywords: epidemiology; chronic pain; suicide ideation; elderly